Fast spatially localised electrooptical mode in vertically aligned nematic LCs with negative dielectric anisotropy. Issue 2 (26th January 2020) - Barnik, Mikhail Ivanovich; Simdyankin, Ivan Vladimirovich; Geivandov, Artur Rubenovich; Umanskii, Boris Alexandrovich; Palto, Serguei Petrovich
ABSTRACT: Electro-optical switching and the liquid crystal (LC) director distribution are studied in spatially periodic electric field for vertically aligned LC with negative dielectric anisotropy. Two electro-optical switching modes characterised by different switching times are observed. These modes are well distinguished optically by choosing proper geometry for the polarisers axes orientation. One of these modes is significantly faster as compared to the other. The fast switching is explained in terms of localised near-to-surface director reorientation. The 3D-numerical simulation shows very good agreement with the experiment: it points out the existence of the disclination lines and field-stabilised walls responsible for the localised director field switching and its relaxation. Possibilities of enhancing the fast mode for high-speed light modulators are discussed. Graphical abstract: uf0001